Response of Key Metabolites during a UV-A Exposure Time-Series in the Cyanobacterium Chlorogloeopsis fritschii PCC 6912 - Ed Dudley (Microorganisms, 2021)
Ultraviolet A (UV-A) is the major component of UV radiation reaching the Earth’s surface, causing indirect damage to photosynthetic organisms via the production of reactive oxygen species (ROS). In comparison, UV-B causes both direct damage to biomolecules and indirect damage. UV-B is well studied in cyanobacterial research due to their long evolutionary history and adaptation to high levels of UV, with less work on the effects of UV-A. In this study, the response of key metabolites in Chlorogloeopsis fritschii (C. fritschii) during 48 h of photosynthetically active radiation (PAR, 15 µmol·m−2·s−1) supplemented with UV-A (11 µmol·m−2·s−1) was investigated using gas chromatography- mass spectrometry (GC-MS). Results showed an overall significant increase in metabolite levels up to 24 h of UV-A exposure. Compared with previously reported UV-B (PAR + UV-B) and PAR only results, UV-A showed more similarity compared to PAR only exposure as opposed to supplemented UV-B. The amino acids glutamate, phenylalanine and leucine showed differences in levels between UV (both supplemented UV-A and supplemented UV-B) and PAR only (non-supplemented PAR), hinting to their relevance in UV stress response. The fatty acids, palmitic and stearic acid, showed positive log2 fold-change (FC) in supplemented UV-A and PAR only experiments but negative log2 FC in UV-B, indicating the more harmful effect of UV-B on primary metabolism. Less research has been conducted on UV-A exposure and cyanobacteria, a potential environmental stimuli for the optimisation of metabolites for industrial biotechnology. This study will add to the literature and knowledge on UV-A stress response at the metabolite level in cyanobacteria, especially within the less well-known species C. fritschii.